Closing the nutrient-food loop: technology innovation and (de)politicization in European nutrient policy - Schwindenhammer, Sandra; Gonglach, Denise (Frontiers in Political Science, 2024)
This contribution examines the development of the European Union’s nutrient policy from 2000 to 2022. It focuses on the policy’s shift orienting toward expert knowledge and technological innovations in nutrient recovery and recycling, and explores the resulting (de)politicization of the policy area. Drawing on evolutionary policy change, agri-food (de)politicization, and agri-food technology innovation research, a three-phase development is identified through qualitative document and public feedback data analysis. The policy development started with a focus on environmental issues and nutrient scarcity in the 2000s (phase 1), expanded to nutrient recycling as a means to close the nutrient-food loop in the mid-2010s (phase 2), and began utilizing secondary nutrient sources for agri-food production and to ensure a stable supply of fertilizers in the 2020s (phase 3). The study shows that while expert knowledge and technological advancements have steered sectoral policies toward a circular agri-food system, they have also led to the EU’s nutrient policy adopting a technocratic approach, privileging specific expert insights and depoliticizing the policy area. The findings highlight the intricate relationship between technological innovation, policy evolution, and public engagement in shaping the European agri-food system.